The road to gender-equitable growth: A state-level analysis of social reproduction in the U.S. - Aashima Sinha (The University of Utah, Department of Economics, 2023)
Building on a Kaleckian-structuralist macroeconomic growth model this paper examines the impact of the interaction between labor market gender equality and social reproduction (SR) or care provisioning, on economic growth across U.S. states. Using panel data for 2003-2017 and principal component analysis, I construct two composite scores for each state to capture care provisioning by household, state, and the market sectors on the supply side and caring tendency to invest in human capacities on the demand side. The interaction of these scores results in four stylized SR regimes. Next, I examine the relationship between women's labor force participation rate (WLFPR) and state's per-capita growth rate across these regimes. The paper contributes new evidence to the engendering macroeconomics scholarship on promoting gender-egalitarian and pro-care economic growth by showing that: 1) regimes characterized by strong public, market, and gender-equal care provisioning experience higher per-capita growth rates compared to regimes that lack such care provisioning; 2) higher WLFPR is compatible with higher economic growth in states with gender-equal care structures and 3) gender-equitable growth can be achieved via state-level policies that expand social spending, access to care services, and gender equality in labor market.
Keywords: J22; O4; O11; 330; social reproduction; care; growth; development; United States; gender; macroeconomics